Pathological Correlates to Prolactin and Growth Hormone - Amira Al Kharusi (Recent Research Advances in Biology Vol. 12, 2021)
Growth Hormone (GH) and Prolactin (PRL) are critical regulators of body growth and metabolism. Secretion and actions of GH and PRL are regulated at several levels and by different factors. The biological actions of these hormones are initiated by their binding to the respective membrane bound receptors of GH and PRL (GHR and PRLR). Several hormone systems are characterized by changes in target tissue sensitivity. Key factors in hormone sensitivity include the number of particular receptors and the duration of receptor activated intracellular signals. A common theme concerning this is e.g. that tyrosine phosphorylated intracellular proteins become inactivated by tyrosine phosphatases or by proteasomal breakdown. In this chapter, a particular focus is put on two different proteins, Suppressors of Cytokine Signaling2 (SOCS2) and Tuberous Sclerosis Complex2 (TSC2) that uniquely impinge on JAK-STAT activation and on mTOR activation. The SOCS2-dependent increase of GH and PRL sensitivity in diabetes or other conditions; like hormone sensitive cancers, raises questions on the importance of altered GH/PRL sensitivity, in addition to conditions related to over-, or under-production of these hormones. It may have a future potential to target GH/PRL sensitivity in cases where conventional hormone treatment fails because of reduced sensitivity. There are still many gaps in our knowledge that need to be filled, and this may in particular be the case for PRL, for which new data indicate that the hormone has a different profile of activity in humans, compared to animals.